Facile Electrochemical Oxidation of Polyaromatic Hydrocarbons to Surface‐Confined Redox‐Active Quinone Species on a Multiwalled Carbon Nanotube Surface. Issue 7 (7th January 2013) - Barathi, Palani; Kumar, Annamalai Senthil
<x xml:space="preserve">Abstract</x> Polyaromatic hydrocarbon (PAH) oxidation: PAHs, which are considered major environmental pollutants, are carcinogenic, and cannot be electrochemically oxidized on conventional electrodes (gold, platinum, and glassy carbon), can be electrochemically oxidized on multiwalled carbon nanotube surfaces at a potential of 1 V versus Ag/AgCl at pH 7. This results in the formation of stable surface‐confined quinone systems (see scheme; AN=anthracene; AQ=anthraquinone).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>